Kesalahan Penerjemahan Harf jar Pembentuk Idiom pada Mahasiswa Pendidikan Bahasa Arab - Puti Zulharby; Analisa Apriliani (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Purpose: The purpose of this study is to analyze the translation errors of harf jar which form idioms from Arabic to Indonesian. Idioms are combinations of words that produce a new meaning that is different from the component words that form it. Methodology: The method used in this research is descriptive qualitative. The research was conducted on students who are studying Arabic translation, and are accustomed to using literal or grammatical translation techniques. Findings: Problems occur when students want to get the equivalent of words in idioms with jar letters. The results showed that the errors made by students were generally intralingual errors, caused by limited understanding of changes in the meaning of words that form idioms, and macrolinguistic errors caused by incorrect cross-cultural interpretations. Implication: The findings in this study can be used as an illustration and consideration for improving translation skills, not only lexical and grammatical translation, but also idiomatic translation. In addition, this research also contributes to the novice Arabic learners about the diversity of meanings of harf jar that form an idiom